Photograph Of Pablo Picasso, Olga Kokhlova And Paulo Picasso - Unknown authorUnknown author (NC, 2026)
Photo of Picasso's family near of one aircraft and with members of the company Ballets Russe. From left to right: Ludmilla Schollar, Alice Nikitina, Serge Lifar, Walter Nouvel, Serge Grigoriev, Lubov Tchernicheva, Mme. Trusevich, Picasso's wife Olga Kokhlova, Picasso's son Paulo Picasso, and Pablo Picasso
Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie